2019
DOI: 10.1371/journal.pcbi.1006757
|View full text |Cite
|
Sign up to set email alerts
|

Tuft dendrites of pyramidal neurons operate as feedback-modulated functional subunits

Abstract: Dendrites of pyramidal cells exhibit complex morphologies and contain a variety of ionic conductances, which generate non-trivial integrative properties. Basal and proximal apical dendrites have been shown to function as independent computational subunits within a two-layer feedforward processing scheme. The outputs of the subunits are linearly summed and passed through a final non-linearity. It is an open question whether this mathematical abstraction can be applied to apical tuft dendrites as well. Using a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Modern experimental techniques allow researchers to conduct detailed morphological analysis 87 and digital reconstructions of neurons 88 , collect biophysical and electrophysiological data, and develop complex multi-compartmental models in order to study synaptic efficacy 59 , synaptic 89 and dendritic integration 90 , dendritic input discrimination capabilities 91 and other neuronal properties. The main feature of the Hippocampome.org knowledge base is evidence-linked information about location of dendrites and axons in different sections and layers of the hippocampus, which served as the basis for neuron type classification.…”
Section: Discussionmentioning
confidence: 99%
“…Modern experimental techniques allow researchers to conduct detailed morphological analysis 87 and digital reconstructions of neurons 88 , collect biophysical and electrophysiological data, and develop complex multi-compartmental models in order to study synaptic efficacy 59 , synaptic 89 and dendritic integration 90 , dendritic input discrimination capabilities 91 and other neuronal properties. The main feature of the Hippocampome.org knowledge base is evidence-linked information about location of dendrites and axons in different sections and layers of the hippocampus, which served as the basis for neuron type classification.…”
Section: Discussionmentioning
confidence: 99%
“…Our study on a single pyramidal neuron is similar to this, indicating that the memory retention is stronger at the lower spatial and temporal overlap. The reason for the similarity between a single pyramidal neuron and neural network is that a pyramidal neuron has been shown to function as a two-layer neural network (Poirazi et al 2003;Polsky et al 2004;Eberhardt et al 2019). We found that pyramidal neurons' memory retention capacity decreased linearly with increasing spatial and temporal overlap of synaptic connections, which needs further experimental verification.…”
Section: Discussionmentioning
confidence: 82%
“…Previous work has suggested that these branches act as independent functional modules [2125], whose responses to local synaptic inputs are linearly summed at the soma. Simulation studies have confirmed that the resulting flat modularization is indeed an accurate description for computations on firing rates [26, 27], where the input and the response are encoded by the rate of synaptic inputs and somatic action potentials, respectively. However, these studies were limited to paired branch stimulation and required complete information about synaptic inputs.…”
Section: Resultsmentioning
confidence: 96%